Acclimatization of Lemongrass Cultivation in Agro-climatic Conditions of Uttarakhand. Issue 3 (4th May 2017) - Chauhan, Nirpendra; Sah, Sunil; Yadav, Rakesh; Bartwal, Sunil; Sagar, Shankar Lal
Abstract: The global demand for lemongrass oil is increasing tremendously due to high citral content. In order to study the acclimatization of lemongrass cultivation with respect to citral content in the agroclimatic conditions of a Himalayan state i.e. Uttarakhand (India), a total 132 essential oil samples were collected from different farmers' fields of Uttarakhand during six years (2009-2014) and subjected to GC fingerprinting for citral estimation. A total 22 samples were analyzed in each year and it has been observed that the mean citral content steadily increased from 69.1 to 78.7% during six years. In the year 2009 and 2010, most of the oil samples (77 and 82%, respectively) showed citral content between 60.0-72.0%. In 2011, 50% of the samples have shown an increased range of citral (72.1-76.0%). Similarly, during 2012 and 2013, more than 68% samples constituted 72.1-76.0% citral in the oils; while in the year 2014, citral content has increased in the lemongrass crop and most of the oil samples (86%) shown citral more than 76.0%. The increasing citral content during six years showed that lemongrass crop is being gradually acclimatized with respect to citral content in the agro-climatic conditions of Uttarakhand.